Notary's Responsibility for the Loss of the Customer's Land Ownership Certificate - Siti Yaningsih, Wa Ode; Djunaedi, Djunaedi (TABELLIUS: Journal of Law, 2026)
This study aims to analyze the notary's responsibility for the loss of a land title certificate and the legal protection provided to clients. A land title certificate is legally binding evidence of land rights, and its loss can lead to legal uncertainty and losses for the rights holder. In notarial practice, notaries often receive and store original documents belonging to the parties, so clarity is needed regarding the notary's responsibility in the event of the loss of such documents. This study uses a sociological juridical research method supported by library research. The sociological juridical approach is used to examine the establishment of legal norms in notarial practice through direct interviews with notaries. Library research is conducted by reviewing laws and regulations, legal literature, legal theories, and Kendari District Court Decision No. 14/pdt. G.S/2020/PN Kdi, which relates to the loss of a client's land ownership certificate. The results of the study indicate that (1) legal protection for customers against the loss of land ownership certificates is provided through preventive and repressive legal protection. (2) notaries are responsible for the loss of ownership certificates if the loss occurs due to negligence in carrying out their duties, with responsibilities that include civil, administrative, and ethical aspects. (3) legal solutions carried out by notaries for the loss of customer ownership certificates in the form of assistance in processing replacement certificates at the land office as a form of professional responsibility and good faith of the notary. In addition, the deed of granting mortgage rights has a close relationship with the ownership certificate as a collateral object, so that the security of the certificate in the process of making and registering mortgage rights is an important obligation of the notary in ensuring legal certainty for the parties.